A Mexican Study of Multiple Intelligences for Pre-Service Teachers of English as a Foreign Language - Rebeca Elena Tapia Carlín; María del Carmen Castillo Salazar; Susana Velázquez Cortés (Asociación Colombiana de Profesores de Ingles, 2013)
This article describes a study conducted in a Mexican English teacher education program about multiple intelligences. Seventy-four first year students participated in the study. Findings reveal that the highest kinds of intelligences were the bodily kinesthetic, the interpersonal, the intrapersonal, and the musical; the lowest ones were the naturalist, the existential, the verbal linguistic, the logical mathematical, and the visual spatial. The authors suggest that it is important to diagnose and promote these intelligences in trainees in a systematic way in order to equip them with knowledge and experience of multiple intelligences in order to use them in their future teacher practice.